Keterampilan Proses Sains dalam Praktikum Fisika - Lumbantoruan, Artha; Irawan, Didik; Siregar, Harina Remalis; Lumbantoruan, Dear (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2019)
AbstractScience process skills are all the skills needed to solve science problems. Thus, science process skills have an important role for students of Physical Education to process science, for example in Thermodynamics experiments. The use of Thermodynamics practicum guidebooks in the laboratory has not been effective for students who are used to using technology in their daily lives. E-modules are nothing new for Physics Education students. The effectiveness of learning can also be achieved through the use of e-modules in the laboratory. This study aims to identify the mastery of science process skills in Physics Education students at Universitas Jambi, both students who use printed guidebooks and students who use e-modules as guides in practicum activities by reviewing 4 aspects of integrated skills (identifying variables, arranging graphs, obtaining and processing data, and analyzing investigations). This research uses a quantitative approach with experimental research methods, namely true experimental. In the research sample used were Physics Education students totaling 65 people, which were divided into two groups randomly so that 35 students were obtained for the experimental class and 30 students for the control class. The assessment instrument used was the science process skills observation sheet with the skill score used in the form of a Likert scale. Based on the results of the analysis of students' mastery scores of integrated science process skills, in the experimental class, the highest percentage identifying variables was 51.4% with the very good category, whereas in the control class, the analyzing investigations aspect had the highest percentage of 43.3% with the very good category.Â AbstrakKeterampilan proses sains adalah segala keterampilan yang dibutuhkan dalam menyelesaikan masalah-masalah sains. Dengan demikian, keterampilan proses sains memiliki peranan penting bagi mahasiswa Pendidikan Fisika untuk memproses sains, misalnya dalam percobaan Termodinamika. Penggunaan buku panduan praktikum Termodinamika di laboratorium belum efektif untuk mahasiswa yang telah biasa menggunakan teknologi dalam kedhidupan sehari-hari. E-modul bukanlah hal yang baru bagi mahasiswa Pendidikan Fisika. Keefektifan belajar juga dapat dicapai melalui penggunaan e-modul di laboratorium. Penelitian ini bertujuan untuk mengidentifikasi penguasaan keterampilan proses sains mahasiswa Pendidikan Fisika di Universitas Jambi, baik mahasiswa yang menggunakan modul yang di cetak maupun mahasiswa yang menggunakan e-module sebagai buku yang memandunya dalam praktikum dengan meninjau 4 aspek keterampilan terintegrasi (identifikasi variabel, membuat grafik, memperoleh dan memproses data, serta analisis investigasi). Penelitian ini menggunakan pendekatan kuantitatif dengan metode penelitian eksperimen, yakni true experimental. Pada penelitian sampel yang digunakan adalah mahasiswa Pendidikan Fisika berjumlah 65 orang, yang dibagi menjadi dua kelompok secara random sehingga diperoleh 35 mahasiswa untuk kelas eksperimen dan 30 mahasiswa untuk kelas kontrol. Instrumen penilaian yang digunakan adalah lembar observasi keterampilan proses sains dengan skor keterampilan yang digunakan berupa skala likert. Berdasarkan hasil analisis skor penguasaan keterampilan proses sains terintegrasi mahasiswa, di kelas eksperimen, identifikasi variabel persentase tertinggi sebesar 51.4% dengan kategori sangat baik, sedangkan di kelas kontrol, aspek analisis investigasi memiliki persentase tertinggi sebesar 43.3% dengan kategori sangat baik.